2017
DOI: 10.1002/cmdc.201700042
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Studies, SPR Affinity Characterization, and Conformational Analysis of Peptides That Mimic the HNK‐1 Carbohydrate Epitope

Abstract: The design of molecules that mimic biologically relevant glycans is a significant goal for understanding important biological processes and may lead to new therapeutic and diagnostic agents. In this study we focused our attention on the trisaccharide human natural killer cell-1 (HNK-1), considered the antigenic determinant of myelin-associated glycoprotein and the target of clinically relevant auto-antibodies in autoimmune neurological disorders such as IgM monoclonal gammopathy and demyelinating polyneuropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…An N-terminal and a C-terminal cysteine were added to enable cyclization. Biotin was coupled to the peptide via a 4,7,10-trioxa-1,13-tridecanediamine succinic acid (Ttds) linker ( Ieronymaki et al, 2017 ). Cyclization and coupling of linker and biotin were performed by JPT Peptide Technologies.…”
Section: Methodsmentioning
confidence: 99%
“…An N-terminal and a C-terminal cysteine were added to enable cyclization. Biotin was coupled to the peptide via a 4,7,10-trioxa-1,13-tridecanediamine succinic acid (Ttds) linker ( Ieronymaki et al, 2017 ). Cyclization and coupling of linker and biotin were performed by JPT Peptide Technologies.…”
Section: Methodsmentioning
confidence: 99%
“…These peptides were selected for the following characteristics: amino acid sequence, hydrophobicity, different length (from 4 to 35 amino acids) and post-translational modification (DeoxyFru, Ac, PO 3 H 2 , and Pam). The hexapeptide LSETTI (11) was selected as a previously developed peptide mimicking the HNK1 tri-saccharide epitope [37]. It is interesting to notice that Frolov et al [19] previously reported that the efficiency of the m-aminophenylboronic acid (m-APBA) immobilised on agarose resin to capture Amadori peptides, after digestion of plasma protein from type 2 diabetes, was affected by unspecific recognition of peptide sequences containing several, often neighbouring, hydroxyamino acid residues.…”
Section: The Phb-lys(phb)-chemmatrix ® Rink Resin Is Specific For Deomentioning
confidence: 99%
“…An N-terminal and a C-terminal cysteine were added to enable cyclization. Biotin was coupled to the peptide via a 4,7,10-trioxa-1,13-tridecanediamine succinic acid (Ttds)-linker (Ieronymaki, Nuti et al, 2017). Cyclization and coupling of linker and biotin were performed by JPT Peptide Technologies.…”
Section: Antigen Selection and Antibody Productionmentioning
confidence: 99%